IMPLEMENTASI PROJECT BASED LEARNING (PBL) DAN PENILAIAN AUTENTIK DALAM PEMBELAJARAN DRAMA INDONESIA - Wajdi, Fathullah (Universitas Pendidikan Indonesia, 2017)
This study aims to explain the implementation of project learning model (PBL) and authentic assessment that can serve as a model for teachers in teaching drama and literature in general. The is a qualitative research study with the following stages: determine assumptions, determine the design, determine the rules of research, collect data, perform data recording, analyze data, verify the research stage, and describe the research results. This research generates several findings: (1) project based learning (PBL) and authentic assessment fit well with the teaching of drama; (2) the model in question is easy to implement in teaching drama; (3) the learning steps involved are simple yet stimulate the students to actively participate; and (4) this model leads to satisfactory student competence, with an average of 3.55 and 3.63 on a 1-4 scale with excellent qualifications. Competitiveness is measured through the authentic judgment with the rubric of the drama performance parameter. Based on the discussion, it can be concluded that (1) project based learning (PBL) and authentic assessment can be implemented well and easily; and (2) the result of model implementation in teaching drama indicates very satisfactory results.Keywords: PBL, authentic assessment, Indonesian drama